Purification clove oil via typical batch distillation column - Norhayati, Abd Raub (2008)
he clove, known botanically as Eugenia aromatica, has a big potential in essential oil market . Eugenol from clove oil is beneficial for therapeutic purposes and flavoring. It is extracted from clove bud and mostly exported as crude clove oil. However, there are changes in market demand of clove oil where the purified clove oil is needed with purity more than 90%. This research is conducted in order to separate the eugenol from clove oil using typical or conventional batch distillation column. The objectives of this research are to understand the operation of batch distillation as well as its conditions to obtain eugenol with has high purity and is colorless. Eugenol is taken out from the clove oil based on different boiling points by using the principles of vapor and liquid equilibrium. The distillate products are analysed using the gas chromatography to ensure both eugenol component and purity. At the end of this research, a high purity of eugenol, 87.28% purity was achieved. The performance and separation behavior of batch distillation was understood as well.